Burning Cities, Burning Brains: Prevalence of Post-Traumatic Stress Disorder in Survivors of Urban Violence in Pakistan – A Neuro Perspective - Amna Sabir, Junaid Rasool, Syeda Fatima Rizvi, Saleem Adil, Syed Ahmed Mahmud, Muhammad Azhar Khan, Abosede Olufunmilayo Odukale-Okuneye (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Urban violence in Pakistan constitutes a profound assault on both structure and psyche,yet neuro‐specific investigations remain scarce. This experimental study aimed to determine the prevalence of post‐traumatic